2010
DOI: 10.1093/toxsci/kfq324
|View full text |Cite
|
Sign up to set email alerts
|

The Long Winding Road toward Understanding the Molecular Mechanisms for B-Cell Suppression by 2,3,7,8-Tetrachlorodibenzo-p-dioxin

Abstract: Suppression of humoral immune responses by 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) was first reported in the mid-1970s. Since this initial observation, much effort has been devoted by many laboratories toward elucidation of the cellular and molecular mechanisms responsible for the profound impairment of humoral immune responses by TCDD, which is characterized by decreased B cell to plasma cell differentiation and suppression of immunoglobulin production. These efforts have led to a significant body of resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 146 publications
(220 reference statements)
4
66
1
Order By: Relevance
“…These results, together with the significant decreases in IgG and IgM titers, indicated that the immune responses were suppressed. These results were consistent with previous reports following human accident exposures (Sulentic and Kaminski, 2011b), indicating that the selected murine model accurately recapitulated a paradigm of the chronic human exposure of TCDD and could provide information for further studies. One of the reasons leading to dramatically reduced IgG and IgM production could be the decrease in number of the antibody-producing plasma cells, due to the arrest in the B cell maturation.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These results, together with the significant decreases in IgG and IgM titers, indicated that the immune responses were suppressed. These results were consistent with previous reports following human accident exposures (Sulentic and Kaminski, 2011b), indicating that the selected murine model accurately recapitulated a paradigm of the chronic human exposure of TCDD and could provide information for further studies. One of the reasons leading to dramatically reduced IgG and IgM production could be the decrease in number of the antibody-producing plasma cells, due to the arrest in the B cell maturation.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, NR4a1 is a critical transcriptional regulator of Foxp3 that itself is a master regulator of the development and function of Treg cells (Ellmeier and Taniuchi, 2014). While there is a consensus that TCDD exposure is a risk factor for certain cancers including NHL (Sulentic and Kaminski, 2011a), the carcinogenic potential of TCDD had been a subject of controversy (Baccarelli et al, 2004). Indeed, TCDD has both anti-inflammatory and cancer-promoting activities, and there are many factors, often counter-acting, involved in the physiology of the long term AhR activation as a result of chronic TCDD exposure, thus the adverse effects on human health can be indirect and delayed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tolerance induction was associated with expansion of CD4 + C-D25 + Foxp3 + Tregs. While TCDD has been shown to inhibit B cell differentiation and antibody production in vitro (91)(92)(93)(94), no studies have yet demonstrated a potential benefit in transplantation. In humans, there is some observational evidence that traffic air pollution may shorten the life of lung transplants through the development of bronchiolitis obliterans syndrome (95).…”
Section: Impact Of Pollutants On Graft Outcomementioning
confidence: 99%